Outward Rectification of Voltage-Gated K(+) Channels Evolved at Least Twice in Life History - Riedelsberger, Janin (PLoS One, 2015)
Voltage-gated potassium (K(+)) channels are present in all living systems. Despite high structural similarities in the transmembrane domains (TMD), this K(+) channel type segregates into at least two main functional categories—hyperpolarization-activated, inward-rectifying (K(in)) and depolarization-activated, outward-rectifying (K(out)) channels. Voltage-gated K(+) channels sense the membrane voltage via a voltage-sensing domain that is connected to the conduction pathway of the channel. It has been shown that the voltage-sensing mechanism is the same in K(in) and K(out) channels, but its performance results in opposite pore conformations. It is not known how the different coupling of voltage-sensor and pore is implemented. Here, we studied sequence and structural data of voltage-gated K(+) channels from animals and plants with emphasis on the property of opposite rectification. We identified structural hotspots that alone allow already the distinction between K(in) and K(out) channels. Among them is a loop between TMD S5 and the pore that is very short in animal K(out), longer in plant and animal K(in) and the longest in plant K(out) channels. In combination with further structural and phylogenetic analyses this finding suggests that outward-rectification evolved twice and independently in the animal and plant kingdom.